Influence of foot position and vision on dynamic postural strategies during the "grand plié" ballet movement (squatting) in young and adult ballet dancers. (21st June 2018) - Bruyneel, Anne-Violette; Bertrand, Marc; Mesure, Serge
Highlights: The "grand plié" is a basic dance movement, learned at the by the youngest of dancers. Dynamic postural strategies during the "grand plié" ballet movement are influenced by foot position, age and visual condition. The parallel foot position was less stable compared with open foot position. The young dancers were more unstable than adult dancers, particularly with eyes closed. The lack of vision increased instability for all dancers. Abstract: Purpose: To analyse dynamic postural strategies during the "grand plié" in two different foot positions (parallel or turned out), with and without vision, and as a function of age in ballet dancers. Method: Twenty young dancers (YD) aged from 8 to 16 years, and 20 adult dancers (AD) aged from 17 to 30 years were recruited. Center of pressure (CoP) and ground reaction forces (GRF) were recorded (500 Hz) during the grand plié (lowering, squatting and rising). This movement was tested with the feet parallel and with both lower limbs turned out (foot angle >140°), with eyes open (EO) and eyes closed (EC). Groups were compared using Student t -tests. Repeated analysis of variance was used to examine the effects of eyes and foot conditions, with a significance level of p < 0.05. Results: The results of this study showed that dynamic postural strategies during the "grand plié" ballet movement are influenced by age, foot position and visual condition. CoP displacement length (p < 0.003) and CoP speed (p < 0.003) were higher in YD compared with AD. CoP surface (p < 0.05), mediolateral CoP speed (p < 0.048) and GRF parameters, particularly the mediolateral (p < 0.049), were higher than in the parallel than the turned out position. In both groups all CoP (p < 0.042) and GRF parameters (p < 0.049), except the vertical component, were higher with EC than EO. Conclusion: The effect of foot position was greatest with EO. The parallel position was less stable. The YD were more unstable in the parallel position, particularly with EC. For both groups, the lack of vision increased instability. These results show the importance of integrating balance training in a variety of foot positions and visual conditions, particularly during the initial stages of training to prevent injury.